2008
DOI: 10.1063/1.2976328
|View full text |Cite
|
Sign up to set email alerts
|

Growth interruption studies on vertically aligned 2-3 wall carbon nanotubes by water assisted chemical vapor deposition

Abstract: Highly aligned, 2-3 wall carbon nanotube (CNT) arrays were used to examine the kinetics of CNT growth. A growth interruption method was used to determine the in situ growth rate. The growth interruption method with a water vapor treatment or acetylene treatment during the interruption enabled the production of CNT stacks with different morphologies. The catalytic activity was also monitored using this method. The lifetime of the catalyst was predicted and verified using the catalyst decay model. High temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Post-growth delamination of forests has been reported to occur readily with simple processing [32,33], including the use of water [32]. Excessive water vapor exposure during growth has also been observed to cause delamination [14]. It has also been noted that forests tend to fall off the substrate easily [14], which is often the case here.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…Post-growth delamination of forests has been reported to occur readily with simple processing [32,33], including the use of water [32]. Excessive water vapor exposure during growth has also been observed to cause delamination [14]. It has also been noted that forests tend to fall off the substrate easily [14], which is often the case here.…”
Section: Resultsmentioning
confidence: 77%
“…Excessive water vapor exposure during growth has also been observed to cause delamination [14]. It has also been noted that forests tend to fall off the substrate easily [14], which is often the case here. Delamination of continuous films during growth has been previously reported [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The catalyst rearrangement is in such a way that the CNTs alignment changed with the growth time. However, it was observed that CNT growth follows the bottom growth approach, where Fe catalyst particles attach to the substrate and CNTs grow vertically from them [18,31]. This suggests that the top portion of the CNT forest grew earlier from the randomly arranged catalyst particles while the bottom portion of the CNT forest grew later from the more arranged/modified catalyst particles.…”
Section: Resultsmentioning
confidence: 90%
“…For example, optical photography and videography, 67,68 optical interference, 69 single-slit laser diffractography, 70 time-resolved reflectivity, 9 laser triangulation, 71,72 and cycling of growth to create stacked structures visible by SEM. 64,73,74 Importantly, all of the abovementioned methods only enables quantifying the height kinetics. On the other hand, real-time mass measurements are more challenging, and have been achieved in the past generally by using a microbalance either ex situ, 5,75 or in situ.…”
Section: Cnt Growth and Terminationmentioning
confidence: 99%